2016
DOI: 10.1038/srep30157
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal responses to Stroop tasks in subjects with post-traumatic stress disorder assessed by functional near infrared spectroscopy

Abstract: Studies on posttraumatic stress disorder (PTSD) showing attentional deficits have implicated abnormal activities in the frontal lobe. In this study, we utilized multichannel functional near-infrared spectroscopy (fNIRS) to investigate selective attention-related hemodynamic activity in the prefrontal cortex among 15 combat-exposed war-zone veterans with PTSD and 13 age- and gender-matched healthy controls. While performing the incongruent Stroop task, healthy controls showed significant activations in the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 55 publications
(64 reference statements)
4
15
0
Order By: Relevance
“…44 Another recent fMRI study also reported significant activations in several cortical and subcortical regions when a high-pain cold stimulus was applied to the thenar surface of the right hand. The activated regions included, but were not limited to, the bilateral anterior insula, bilateral dorsal ACC extending into the presupplementary motor area (BAs 6,8,24,32), and the right lateral PFC (i.e., DLPFC and VLPFC; BAs 9,10,44,45,46,47). 45 In this study, our results also present similar activations in several prefrontal cortical areas (such as BAs 8, 9, 10, 6 and 7].…”
Section: Consistency Between Our Results and Those By Fmrisupporting
confidence: 73%
“…44 Another recent fMRI study also reported significant activations in several cortical and subcortical regions when a high-pain cold stimulus was applied to the thenar surface of the right hand. The activated regions included, but were not limited to, the bilateral anterior insula, bilateral dorsal ACC extending into the presupplementary motor area (BAs 6,8,24,32), and the right lateral PFC (i.e., DLPFC and VLPFC; BAs 9,10,44,45,46,47). 45 In this study, our results also present similar activations in several prefrontal cortical areas (such as BAs 8, 9, 10, 6 and 7].…”
Section: Consistency Between Our Results and Those By Fmrisupporting
confidence: 73%
“…General linear model (GLM) analysis was used to quantify time-dependent ΔHbO patterns elicited during the handgrip task, by using a series of consecutive stimulation-specific boxcar functions convolved with a hemodynamic response function as a regressor, as in prior studies. [26][27][28] Only ΔHbO values were analyzed and reported in this study, because ΔHbR values were found to have similar and opposite qualitative trends but with smaller amplitudes and lower signal-to-noise ratio, as previously reported in other studies for other motor activation tasks and as seen in Fig. 1(c).…”
Section: Methodssupporting
confidence: 57%
“…Right contrast. For the Stroop task, brain activity (i.e., increase in O 2 Hb and decrease in HHb during the task) was identified in frontal regions which are compatible with those found in previous work (lateral prefrontal cortices [59]). Two-tailed, uncorrected 5% null hypothesis thresholds (p = 0.05) are reported on the color bars.…”
Section: Fnirs-eeg Data Analysissupporting
confidence: 88%